A Brief History of Islam in Europe Thirteen Centuries of Creed, Conflict and Coexistence - Berger, Maurits (Leiden University Press, 2014)
This book presents an overall presentation and discussion of developments ever since Islam appeared on the European stage thirteen centuries ago. The events and stories presented increase the understanding of present debates on, and notions of, Islam and Muslims in Europe. This book shows that in the course of thirteen centuries the Muslim as well as Islam have undergone many metamorphoses. The Muslim has entered the European stage as a conqueror, antichrist, scholar, benign ruler, corsair, tradesman and fellow citizen. The image of Islam has meandered accordingly, as a religion that was feared as an enemy or embraced as a partner against heretical Christians, despised as an abomination or admired as a civilization, and studied for missionary, academic, colonial or security purpose.